Finance and Accounting for Business - Ryan, Bob, 1947- (London : Thomson Learning, 2004)
Covering the major topic areas the market would expect at this level, this book does not patronise but instead allows the reader to develop their knowledge of the subject from the basis of their own experience. The text is replete with examples drawn from real cases.
Includes bibliographical references and index.
Keywords: Accounting; Business enterprises -- Finance; Finance and Accounting